2019
DOI: 10.1111/nmo.13754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intestinal alkaline phosphatase on intestinal barrier function in a cecal ligation and puncture (CLP)‐induced mouse model for sepsis

Abstract: Background Sepsis is a severe pathological condition associated with systemic inflammation, intestinal inflammation, and gastrointestinal barrier dysfunction. Intestinal alkaline phosphatase (IAP) has been demonstrated to detoxify lipopolysaccharide, an important mediator in the pathophysiology of sepsis. We investigated the effect of treatment with IAP on intestinal permeability, intestinal inflammation, and bacterial translocation. Methods OF‐1 mice were divided into 4 groups (n = 12/group), undergoing eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
(121 reference statements)
0
15
0
Order By: Relevance
“…Regarding sepsis-induced acute kidney injury (AKI), it was observed in the piglet model of AKI that 25 U/kg/h of bovine IAP increased serum and renal tissue AP activity, decreased proximal tubular injury, and prevented AKI [66]. Another study showed preventive and curative effects of treatments with 1 IU/g of calf IAP, which in septic mice decreased the permeability of the small intestine by 50%, and increased mRNA expression levels of claudin-1 and claudin-14, which are main structural tight junction proteins in the intestine [67]. These studies confirmed that IAP influences both inflammatory and intestinal barriers, contributing to intestinal health [66,67].…”
Section: The Role Of Iap As a Predictor Of Altered Barrier Intestinal And Gut Microbiota Functionmentioning
confidence: 98%
“…Regarding sepsis-induced acute kidney injury (AKI), it was observed in the piglet model of AKI that 25 U/kg/h of bovine IAP increased serum and renal tissue AP activity, decreased proximal tubular injury, and prevented AKI [66]. Another study showed preventive and curative effects of treatments with 1 IU/g of calf IAP, which in septic mice decreased the permeability of the small intestine by 50%, and increased mRNA expression levels of claudin-1 and claudin-14, which are main structural tight junction proteins in the intestine [67]. These studies confirmed that IAP influences both inflammatory and intestinal barriers, contributing to intestinal health [66,67].…”
Section: The Role Of Iap As a Predictor Of Altered Barrier Intestinal And Gut Microbiota Functionmentioning
confidence: 98%
“…In a mouse model of peritonitis, IAP supplementation reduced intestinal permeability and suppressed gut bacterial translocation into the blood stream, liver, and lung [ 19 ]. In another study, IAP reduced the magnitude of increased permeability in the small intestine of a cecal ligation and puncture (CLP) mouse model [ 20 ].…”
Section: Iap and Barrier Functionmentioning
confidence: 99%
“…In addition, peritoneal irrigation with IAP reduced the increased permeability of the small intestine induced by the cecal ligation and puncture procedure in mice by 50%. More than that, IAP also significantly enhanced survival in mice undergoing cecal ligation and puncture, likely through a reduction of local inflammation and remote organ damage [76, 77]. These findings suggest that IAP supplementation may promote the recovery of patients after abdominal surgery.…”
Section: Additional Clinical Implications For Iapmentioning
confidence: 99%